The dependence of hot deformation-recrystallisation properties of Al-6063 (Etial-60) alloy on homogenisation practice - Erarslan, Y; Çigdem, M (CARL HANSER VERLAG, 2002)
In this work, the effect of the cooling rate after homogenisation on the critical defomation ratio, maximum grain size and recrystallisation grain size has been studied. Experimental results have revealed that hot deformation - restoration properties and recrystallised grain structures are affected to a great extend by the cooling rate. The values of the critical defomation ratio and maximum grain size of a hot rolled specimen cooled at a rate of 0.9 K/min were found to be 23 % and 1.3 mm while those for a specimen cooled at 6 K/min were measured as 37 % and 0.8 mm, respectively.
Keywords: hot deformation; homogenisation; recrystallisation; critical deformation ratio; grain size; AL-MG-SI; PURITY ALUMINUM; GRAIN-GROWTH; STRAIN; Metallurgy & Metallurgical Engineering